Repression of Ets-2-Induced Transactivation of the Tau Interferon Promoter by Oct-4 - Ezashi, Toshihiko (American Society for Microbiology, 2001)
Oct-4 is a POU family transcription factor associated with potentially totipotent cells. Genes expressed in the trophectoderm but not in embryos prior to blastocyst formation may be targets for silencing by Oct-4. Here, we have tested this hypothesis with the tau interferon genes (IFNT genes), which are expressed exclusively in the trophectoderm of bovine embryos. IFNT promoters contain an Ets-2 enhancer, located at −79 to −70, and are up-regulated about 20-fold by the overexpression of Ets-2 in human JAr choriocarcinoma cells, which are permissive for IFNT expression. This enhancement was reversed in a dose-dependent manner by coexpression of Oct-4 but not either Oct-1 or Oct-2. When cells were transfected with truncated bovine IFNT promoters designed to eliminate potential octamer sites sequentially, luciferase reporter expression from each construct was still silenced by Oct-4. Full repression required both the N-terminal and POU domains of Oct-4, but neither domain used alone was an effective silencer. Oct-4 and Ets-2 formed a complex in vitro in the absence of DNA through binding of the POU domain of Oct-4 to a site located between the “pointed” and DNA binding domains of Ets-2. The two transcription factors were also coimmunoprecipitated after being expressed together in JAr cells. Oct-4, therefore, silences IFNT promoters by quenching Ets-2 transactivation. The POU domain most probably binds to Ets-2 directly, while the N-terminal domain inhibits transcription. These findings provide further evidence that the developmental switch to the trophectoderm is accompanied by the loss of Oct-4 silencing of key genes.